2016
DOI: 10.1162/jocn_a_00963
|View full text |Cite
|
Sign up to set email alerts
|

Beat that Word: How Listeners Integrate Beat Gesture and Focus in Multimodal Speech Discourse

Abstract: Abstract■ Communication is facilitated when listeners allocate their attention to important information (focus) in the message, a process called "information structure." Linguistic cues like the preceding context and pitch accent help listeners to identify focused information. In multimodal communication, relevant information can be emphasized by nonverbal cues like beat gestures, which represent rhythmic nonmeaningful hand movements. Recent studies have found that linguistic and nonverbal attention cues are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 46 publications
6
37
1
1
Order By: Relevance
“…Our findings add to the existing literature a clear indication of the usefulness of not only observing [as in 1] but also producing beat gestures in a brief narrative discourse training. This constitutes further evidence that beat gestures serve as visual highlighters of linguistic functions that are associated with focus marking, rhythmic marking, and discourse structure marking [29,30], confirming electrophysiological studies showing that beats are connected to language-related areas of the brain (e.g., [40]). …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings add to the existing literature a clear indication of the usefulness of not only observing [as in 1] but also producing beat gestures in a brief narrative discourse training. This constitutes further evidence that beat gestures serve as visual highlighters of linguistic functions that are associated with focus marking, rhythmic marking, and discourse structure marking [29,30], confirming electrophysiological studies showing that beats are connected to language-related areas of the brain (e.g., [40]). …”
Section: Discussionsupporting
confidence: 78%
“…We hypothesize that it will, given the evidence that beat gestures play an important 9th International Conference on Speech Prosody 2018 13-16 June 2018, Poznań, Poland role as highlighters of linguistic functions [29,30] such as focus marking, rhythmic marking, and discourse structure marking. Thus, we suggest that beats are pragmatically meaningful gestures [11,31,32] that can help build up children's narrative performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we might have affected the phrase final position intonations, relevant to anchor beats to acoustic envelope modulations. Recently, Dimitrova et al (2016) showed that when a beat accompanied a nonaccented target word, it resulted in a greater late anterior positivity relative to a beat accompanying the equivalent focused word. This result actually suggested an increased cost of multimodal speech processing when nonverbal information targeted verbal information that was not auditorily emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Vocalized pauses or fillers such as "ah" or "um" are distractions that may express nervousness or lack of sincerity of the speaker [9]. The meaning of behavior could be strengthened or contradicted when they are combined with multimodality [10,11]. For example, expressions of amusement can be detected by observing a speaker's facial expression but the effect can be bolstered by the speaker's voice [11].…”
Section: Introductionmentioning
confidence: 99%